N-acetylgalactosaminide α2,6-sialyltransferase II is a candidate enzyme for sialylation of galactose-deficient IgA1, the key autoantigen in IgA nephropathy - Stuchlová Horynová, Milada; Vrablikova, Alena; Stewart, Tyler J; Takahashi, Kazuo; Czernekova, Lydie; Yamada, Koshi; Suzuki, Hitoshi; Julian, Bruce A; Renfrow, Matthew B; Novák, Jan; Raška, Milan (Nephrology, dialysis, transplantation, 2015)
BACKGROUND: Galactose-deficient O-glycans in the hinge region (HR) of immunoglobulin A1 (IgA1) play a key role in the pathogenesis of IgA nephropathy (IgAN). O-Glycans of circulatory IgA1 consist of N-acetylgalactosamine (GalNAc) with a β1,3-linked galactose; both sugars may be sialylated. In patients with IgAN, α2,6-sialylated GalNAc is a frequent form of the galactose-deficient O-glycans. Prior analyses of IgA1-producing cells had indicated that α2,6-sialyltransferase II (ST6GalNAc-II) is likely responsible for sialylation of GalNAc of galactose-deficient IgA1, but direct evidence is missing. METHODS: We produced a secreted variant of recombinant human ST6GalNAc-II and an IgA1 fragment comprised of Cα1-HR-Cα2. This IgA1 fragment and a synthetic HR peptide with enzymatically attached GalNAc residues served as acceptors. ST6GalNAc-II activity was assessed in vitro and the attachment of sialic acid to these acceptors was detected by lectin blot and mass spectrometry. RESULTS: ST6GalNAc-II was active with both acceptors. High-resolution mass spectrometry analysis revealed that up to three sialic acid residues were added to the GalNAc residues of the HR glycopeptide. CONCLUSIONS: Our data provide direct evidence that ST6GalNAc-II can sialylate GalNAc of galactose-deficient IgA1. As serum levels of galactose-deficient IgA1 with sialylated glycoforms are increased in IgAN patients, our data explain the corresponding part of the biosynthetic pathway.
Keywords: sialyltransferasy; Cells, Cultured; Humans; Autoantigens; Mass Spectrometry; galaktosa; imunoglobulin A; autoantigeny; hmotnostní spektrometrie; Galactose; Glycosylation; rekombinantní proteiny; Glomerulonephritis, IGA; kultivované buňky; Recombinant Proteins; kyselina N-acetylneuraminová; IgA nefropatie; lidé; Sialyltransferases; glykosylace; N-Acetylneuraminic Acid; Immunoglobulin A